The genus Begonia (Begoniaceae) in Peru - Moonlight, Peter. W.; Jara-Muñoz, Orlando A.; Purvis, David A.; Delves, Jay; Allen, Josh P.; Reynel, Carlos (European Journal of Taxonomy, 2023)
We provide a floristic account for the Begoniaceae of Peru. The family is represented in Peru by 76 species, which are all members of the genus Begonia and represent eighteen sections. Twelve new species are described: B. condorensis Jara & Moonlight sp. nov., B. deltoides Moonlight sp. nov., B. huancabambae Moonlight sp. nov., B. imbrexiformis Moonlight sp. nov., B. longinqua Moonlight sp. nov., B. longitepala Moonlight sp. nov., B. nunezii Moonlight sp. nov., B. occultata J.P.Allen & Moonlight sp. nov., B. pedemontana Moonlight sp. nov., B. serratistipula Moonlight sp. nov., B. vargasii Moonlight sp. nov. and B. yuracyacuensis Moonlight sp. nov. We also provide four new records for the country: B. andina Rusby, B. brandbygeana L.B.Sm. & Wassh., B. neoharlingii L.B.Sm. & Wassh. and B. unilateralis Rusby. We provide an identification key to all species. The ecology, distribution, and conservation status of all Peruvian Begonia species are discussed, including provisional IUCN threat assessments. Most species are illustrated by either historical illustrations, contemporary photographic plates, or line drawings. Twenty-six names are newly synonymised including fifteen previously accepted species, and we designate eighty-three lectotypes, four neotypes, and four epitypes.